Oral Health Literacy and Behavior of Health Sciences University Students - Tuti N Mohd-Dom; Ng Yee Ying; Lye Shen Ming; Shahida Moho-Said; Noriah Yusof (Faculty of Dentistry, Universitas Indonesia, 2015)
Objective: This study aimed to determine the level of oral health literacy and behavior among health sciences. Methods: The method used descriptive cross-sectional survey involving 609 students from Faculty of Medicine, Dentistry, Pharmacy and Allied Health Sciences in the Universiti Kebangsaan Malaysia. Oral health literacy level and behaviour was assessed with a validated and pretested self-administered questionnaire using the Newest Vital Sign (NVS) tool and modified Oral Health Adult Literacy Questionnaire (OHL-AQ). Results: A total of 509 participants involved in the study (83.6%). The overall mean oral health literacy score was 10.27 (95% CI 7.92, 12.62), which found dental students showing statistically significant higher scores (mean=11.36, 95% CI 9.70, 13.02) compared to medical (mean=10.72, 95% CI 8.67, 12.77), allied health sciences (mean=9.89, 95% CI 7.34, 12.44) and pharmacy (mean=9.55, 95% CI 7.23, 11.87). Almost all respondents are non-smokers (99.8%) and non-drinkers (97.2%). Only 19.1% pay regular dental visits every 6-12 months while 51.1% visit dentist only when they have dental pain. Conclusion: There appears to be a positive relationship between oral health literacy and oral health behavior. Health science university students should be provided substantial dental health education in their curriculum as they show good potential as strategic partners in oral health. DOI: 10.14693/jdi.v22i2.404